Effectiveness of a Family Empowerment Module in Reducing Blood Pressure among Elderly with Hypertension: A Community-Based Quasi-Experimental - Hendri Tamara Yuda; Syed Sharizman Bin Syed Abdul Rahim; Mohd Faizal Madrim; Putra Agina Widyaswara Suwaryo (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Hypertension is a prevalent chronic condition among the elderly, often leading to cardiovascular complications. Family involvement in care has been identified as a potential strategy to improve hypertension control. This study aimed to evaluate the clinical impact of a family empowerment module on reducing systolic and diastolic blood pressure in elderly patients with hypertension. Methods: A quasi-experimental design with a two-group pretest-posttest procedure was used. The study recruited elderly participant in Indonesia between the ages of 60 and 90 who had been diagnosed with hypertension. Families of participants received a structured family empowerment intervention and provided care for one month. Blood pressure was taken before and after the intervention with a digital sphygmomanometer. With SPSS version 27, the Wilcoxon signed-rank test was used to examine the data. Ethical permission was received from the Health Research Ethics Committee of Universitas Muhammadiyah Gombong Results: There was a significant reduction in both systolic and diastolic blood pressure following the intervention. The mean systolic pressure decreased with a test statistic of Z = -4.901, p < 0.001, while diastolic pressure showed Z = -4.938, p < 0.001. Conclusion: The family empowerment module demonstrated significant clinical effectiveness in lowering blood pressure among elderly hypertensive patients. This approach may serve as a valuable strategy in community-based hypertension management.